The correlations between body posture parameters and the somatic type of male and female pupils playing selected musical instruments - Mateusz Apanowicz (Kazimierz Wielki University, 2018)
The literature review has shown that the issue is discussed sporadically and authors more often focus on the correlations of body mass with the feet architecture than the relationships between postural parameters and the somatic type. Material, methods and research tools. 393 students from randomly selected music schools were qualified for the study. The values of body weight and height were assessed using an electronic medical scale and body posture parameters by means of the photogrammetric method.